SOCIALIZATION OF HEALTHY AND SAFE INTERNET USE ON ADOLESCENT CHILDREN IN EAST BULAK VILLAGE, DEPOK CITY - Isroyati Isroyati; Aliffia Teja Prasasty; Rina Nurhidayati (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
In line with the times, the progress of internet technology is getting faster. The existence of the internet has an impact on society, especially teenagers. They can get information quickly, communicate with anyone and anytime and anywhere these teenagers easily access anything.  With this situation, there are many dangers lurking for teenagers if they are unable to utilize internet access properly, dangerous if the internet is used incorrectly and often happens to teenagers. With this concern for teenagers in the village of Bulak Timur, Depok City, the author held a socialization on the use of healthy and safe internet contained in community service activities. The socialization was conducted directly in Bulak Timur village, Depok city. Through this socialization, it is hoped that teenagers will be able to expand their knowledge on how to use the internet in a healthy and safe manner, as well as positive things and what is good to do and what is not good to do.